2023
DOI: 10.1021/acs.estlett.3c00196
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an In Vitro Model to Assess the Toxicity of 6PPD-Quinone and Other Tire Wear Transformation Products

Abstract: The tire wear transformation product 6PPD-quinone (6PPDQ) has been implicated as the causative factor for broad scale mortality events for coho salmon in the Pacific Northwest. Highly variable sensitivity to 6PPDQ in closely related salmonids complicates efforts to evaluate the broader toxicological impacts to aquatic ecosystems. Our goals were to (1) validate the large range of in vivo species sensitivities reported for coho, Chinook, and sockeye salmon and (2) develop an in vitro platform for assessing 6PPDQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Similarly, mitochondrial dysfunction can lead to overproduction of reactive oxygen species (ROS) that are also known modulators of vascular permeability, 62 and mitochondrial dysfunction has also been implicated as a proposed route of 6PPD-quinone toxicity using rainbow trout and coho salmon in vitro models. 63,64 However, we did not observe molecular signatures indicating the presence of mitochondrial dysfunction.…”
Section: Dose-dependent Effects Of 6ppd-quinone On Globalcontrasting
confidence: 75%
“…Similarly, mitochondrial dysfunction can lead to overproduction of reactive oxygen species (ROS) that are also known modulators of vascular permeability, 62 and mitochondrial dysfunction has also been implicated as a proposed route of 6PPD-quinone toxicity using rainbow trout and coho salmon in vitro models. 63,64 However, we did not observe molecular signatures indicating the presence of mitochondrial dysfunction.…”
Section: Dose-dependent Effects Of 6ppd-quinone On Globalcontrasting
confidence: 75%
“…DPPD showed the reproductive and developmental toxicity in rats . The derived quinones (PPD-Qs) have also triggered worldwide concerns lately, especially for 6PPD-Q due to its extreme high toxicity to aquatic organisms, including coho salmon, brook trout, and rainbow trout, at environmentally relevant concentrations. In vitro model studies also confirmed the acute sensitivity of coho salmon cell line CSE-119 to 6PPD-Q . Considering that PPD-Qs stand out as a more serious threat to the environment and public health than their parent compounds, exploring the oxidation kinetics of PPDs is quite significant.…”
Section: Introductionmentioning
confidence: 95%
“…6PPD-Q has been identified as the primary causal toxicant in stormwater-linked urban runoff mortality syndrome (URMS) affecting aquatic organisms, demonstrating acute toxicity at very low concentrations, with an LC 50 for coho salmon of 95 ng/L . Apart from coho salmon, 6PPD-Q have also been found to be toxic to other fish species, such as chinook salmon, zebrafish larvae, rainbow trout, brook trout, white-spotted char, and steelhead. Previous studies have elucidated various mechanisms underlying the toxicity of 6PPD-Q in mammals and aquatic species. The toxicity mechanism of 6PPD-Q in mammalian cells and aqueous organisms may involve the formation of DNA adducts and the disruption of genomic DNA integrity via reactive oxygen species, leading to oxidative damage such as oxidized base adducts and DNA strand breaks .…”
Section: Introductionmentioning
confidence: 99%